Synthesis and study of biological activity of some new Imidazole derivatives (Baghdad Science Journal, 2018)
In this work ester derivatives were synthesized by the reaction of imidazole derivatives (C1) with ethylchloroacetate in ethanol and NaOH to give the corresponding (C2) .While compound (C3) acetohydrazide was synthesized by the reaction of ester derivatives (C2) with hydrazine hydrat in ethanol. Compound (C3) from the reaction with different aromatic aldehydes in absolute ethanol gave the Schiff′s bases (C4,C5). The product compounds were characterized by FT-IR, U.V and 1HNMR spectra and the biological activities were studied as antibacterial.